An Australian source for Pacific-Gondwanan zircons: Implications for the assembly of northeastern Gondwana - Martin, E.; Collins, W.; Kirkland, Chris (Geological Society of America, 2017)
© 2017 Geological Society of America. Detrital zircons in Neoproterozoic-Paleozoic basins of the Pacific-Gondwana (PG) region contain a distinctive 700-500 Ma population conventionally considered to be derived from Antarctica. However, the 700-600 Ma age component of the population predates major peripheral orogenesis (Terra Australis orogen), which began at ca. 580 Ma, and the highly evolved e Hf(t) -in-zircon values (to -40) require an Archean source, which is not proximal to the Terra Australis active margin. Based on similar e Hf(t) arrays defined by Neoproterozoic granites in Western Australia and detrital zircon populations from the surrounding basins, we suggest that PG zircon grains were derived from the > 2000-km-long, late Neoproterozoic Paterson-Petermann orogen, which sutured northern and southern Australia at 550-530 Ma. This Himalayan-style orogen was responsible for amalgamating Southeast Asian terranes into northeast Gondwana, thereby constraining the paleogeography of the northern Gondwanan margin at the Precambrian-Cambrian boundary. Remarkable isotopic similarity of zircon grains with the Lhasa terrane of Tibet suggests that the Paterson-Petermann orogen was the eastern sector of the developing circum-Gondwana subduction system from ca. 700 Ma.